Canadian Coalition for Green Health Care Leading the Evolution of Green - Kent Waddington and Linda Varangu (Healthcare Quarterly, 2016)
Since 2000, a growing contingent of healthcare organizations, individuals and companies have embraced principles and practices of environmental stewardship with a focus on making health service delivery more environmentally sustainable. This article provides an overview of the sector's many successes, drawing upon both Coalition-sponsored initiatives and those initiated by its most engaged and forward-thinking stakeholders, many of whom are original signatories to Canada's Joint Position Statement: Toward an Environmentally Responsible Canadian Health Sector.
Keywords: Green healthcare, climate change, ecologically sustainable, environmentally sustainable, environmental impact, sustainable recycling